A comparison of ERBS spectra of compounds with Monte Carlo simulations. (11th February 2016) - Vos, M.; Marmitt, G. G; Grande, P. L.
Abstract : Electron Rutherford backscattering measures the near‐surface composition of samples quantitatively. For interpretation, one usually relies on the single‐scattering approximation. Here, we present results for four compounds, containing oxygen and other species, varying from very light to very heavy. Two Monte Carlo codes are described that model these measurements. From these simulations, it is clear that for all samples, multiple scattering occurs frequently, but also that the single scattering interpretation deduces the right composition, except for O atoms in a very heavy matrix, where interpretation is more difficult. The intrinsic width of the peaks, a consequence of Doppler broadening due to the velocity of the (vibrating) atoms, turns out to be more sensitive to multiple scattering effects. Copyright © 2016 John Wiley & Sons, Ltd.